Dominance of misfolded intermediates in the dynamics of α-helix folding - Lin, Milo M. (National Academy of Sciences, 2014)
Helices are the “hydrogen atoms” of biomolecular complexity; the DNA/RNA double hairpin and protein α-helix ubiquitously form the building blocks of life’s constituents at the nanometer scale. Nevertheless, the formation processes of these structures, especially the dynamical pathways and rates, remain challenging to predict and control. Here, we present a general analytical method for constructing dynamical free-energy landscapes of helices. Such landscapes contain information about the thermodynamic stabilities of the possible macromolecular conformations, as well as about the dynamic connectivity, thus enabling the visualization and computation of folding pathways and timescales. We elucidate the methodology using the folding of polyalanine, and demonstrate that its α-helix folding kinetics is dominated by misfolded intermediates. At the physiological temperature of T = 298 K and midfolding time t = 250 ns, the fraction of structures in the native-state (α-helical) basin equals 22%, which is in good agreement with time-resolved experiments and massively distributed, ensemble-convergent molecular-dynamics simulations. We discuss the prominent role of β-strand–like intermediates in flight toward the native fold, and in relation to the primary conformational change precipitating aggregation in some neurodegenerative diseases.